Representations of nature of science in U.S. science standards: A historical account with contemporary implications. Issue 9 (2nd April 2019) - Summers, Ryan; Alameh, Sahar; Brunner, Jeanne; Maddux, John M.; Wallon, Robert C.; Abd‐El‐Khalick, Fouad
Abstract: This study evaluated the representations of nature of science (NOS) in U.S. state science standards, and examined the changes in these representations from documents advanced in the 1980s through 2016. Drawing from the consensus perspective on NOS and prior studies focusing on the analysis of textual content, documents were inspected for 10 target NOS aspects: the empirical, tentative, inferential, creative, theory‐driven, and social NOS, in addition to the myth of "The Scientific Method, " the nature of scientific theories and laws, and the social and cultural embeddedness of science. Ninety‐eight state documents from 48 states were analyzed and multiple editions were collected from 34 states. Additionally, relevant materials from the Next Generation Science Standards ( NGSS ) were assessed for their coverage of the same NOS aspects. Collected materials were scored as whole documents, including over 11, 000 pages of text in total, on each target aspect, which reflected the treatment (naïve vs. informed) of NOS in text and the manner of presentation (explicit vs. implicit). Overall, surprisingly, state standards documents have improved very little with respect to their NOS coverage over the last 30 years. NOS standards documents remain silent on a majority of key aspects of NOS, and the number of aspects showing explicit, informed representations has held constant. The NGSS performed well compared to many contemporary documents, but they failed to address all target NOS aspects in a desirable manner. Further analysis raised concerns with the degree that states fully adopt and disseminate standards in manner consistent with the NGSS despite stated intentions, which may negatively impact NOS coverage in instructional resources and classroom enactments. To improve NOS representations in standards, recognizing the role these documents play in shaping instructional materials and teaching in the science classroom, exemplars from analyzed materials were highlighted with informed and explicit representations of multiple aspects.